A TWO-WEEK CPA COACHING COURSE. - Kempner, Jack J. (The Accounting Review, 1961)
Two weeks at this pace is a grueling experience for students and instructors alike. Nevertheless, every applicant who has ever started the course has stayed with it until the end. It will be noticed that the course is concluded with consolidation. Although this may not be the most appropriate sequence it has been deliberately placed at the end because it has been found that most students have a very limited background in this area and are anxious to learn as much as they can about it. It has also been found that if by any chance a student has become over-confident during the sessions, a couple of days on Consolidations will dispel any conceited notions. Despite the intensive nature of the course, two weeks are hardly enough time to prepare adequately for the CPA examinations. It is emphasized that these two weeks are only a beginning. The program is simply an attempt to reorient the student who has lost the habit of systematic study to force him to discipline himself to carry on a program of preparation for the exam after the course has terminated, and to point out specific weaknesses in his background.